2021
DOI: 10.3390/epidemiologia2030020
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of COVID-19 in the State of Sergipe/Brazil and Its Relationship with Social Indicators

Abstract: A pandemic is capable of generating a great impact, not only from the point of view of health, but also socioeconomically. In March 2020, the World Health Organization (WHO) declared that a new pandemic situation had arisen, due to the SARS-CoV-2 virus, whose probable origin was zoonotic. The largest number of cases of this disease is concentrated in the United States of America (USA), India, and Brazil. The mortality rate is estimated at 3.4%, but regional differences may exist, and places with a high demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The pandemic revealed the scarcity of healthcare resources and laid bare deep inequalities, not only between public and private healthcare, but also within SUS itself and in the difference in the supply of ICU beds between municipalities and regions in the country [ 52 , 53 , 54 , 55 ]. In this way, the three-year pandemic scenario in the state of Acre presented a combination of factors that favored the transmission of the virus and justified the high number of cases and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic revealed the scarcity of healthcare resources and laid bare deep inequalities, not only between public and private healthcare, but also within SUS itself and in the difference in the supply of ICU beds between municipalities and regions in the country [ 52 , 53 , 54 , 55 ]. In this way, the three-year pandemic scenario in the state of Acre presented a combination of factors that favored the transmission of the virus and justified the high number of cases and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Propôs interpretar a construção social que determina as condições de vida, relacionando os processos sociais e políticos à determinação da saúde e da doença em todas as dimensões (singular, particular e estrutural) (Breilh, 1991;Fonseca & Egry, 2010).…”
Section: Coleta E Análise De Dadosunclassified
“…The epidemiology of COVID-19 was also studied by Fonseca et al [ 19 ] in the state of Sergipe, Brazil. The authors showed a positive correlation between the number of cases and deaths with demographic density.…”
Section: Introductionmentioning
confidence: 99%